The association of markers of oxidative-inflammatory status with malnutrition in hemodialysis patients with serum ferritin lower than 500 ng/mL - Almeida, Simone Gonçalves de (2013)
Introduction: Enhanced inflammatory-oxidative status is well established in chronic kidney disease. Objective: The objective of this study was to evaluate the oxidative- inflammatory status and iron indices in patients undergoing maintenance hemodialysis (HD) with serum ferritin lower than 500ng/mL, and to correlate them with nutritional status. Method: In a cross-sectional survey 35 HD patients (23 with normal nutritional status, 12 with Protein-Energy-Wasting syndrome, PEW), and healthy volunteers (n = 35) were studied. Serum concentration of iron, ferritin, transferrin saturation, malondialdehyde (MDA), protein carbonyl (PC), high-sensitive serum C - reactive protein (hs-CRP) and blood counts were determined. The nutritional status was determined by anthropometric and biochemical criteria. Results: HD patients showed low values of hemoglobin and higher values of ferritin, MDA and PC when compared with healthy volunteers. HD subjects with PEW had higher values of PC and hs-PCR as compared to HD patients with normal nutritional status. A multiple logistic regression analysis showed that the independent variables PC (Wald Statistic 4.25, p = 0.039) and hs-CRP (Wald Statistic 4.83, p = 0.028) where related with the patients' nutritional condition. Conclusion: In HD patients with serum ferritin below 500 ng/mL was observed one association of the markers of oxidative stress and inflammation with poor nutritional status independently of serum ferritin, gender and age. ________________________________________________________________________________________________________________ RESUMO